'ND Falcon', a new pinto bean with combined resistance to rust and soybean cyst nematode. Issue 2 (27th March 2020) - Osorno, Juan M.; Vander Wal, Albert J.; Posch, John; Simons, Kristin; Grafton, Kenneth F.; Pasche, Julie S.; Nelson, Berlin D.; Jain, Shalu; Pastor‐Corrales, Marcial
Abstract: 'ND Falcon' pinto bean (PVP‐201900174, Reg. no. CV‐326, PI 690446) is a new cultivar developed by the Dry Edible Bean Breeding Program at North Dakota State University and released by the North Dakota Agricultural Experiment Station. Pinto bean is the most important dry bean market class in the United States. North Dakota is the largest producer of dry bean in the country, where ∼50% of production is pinto bean. Both biotic and abiotic stresses are the main factors responsible for seed yield reductions. Between 2013 and 2018, ND Falcon was tested across more than 22 environments in North Dakota. Averaged across environments, seed yield of ND Falcon was not significantly different from commonly grown pinto bean cultivars in the region. Nonetheless, ND Falcon is resistant to the most common race (20‐3) of the bean rust pathogen and to soybean cyst nematode (HG Type 0). Therefore, a seed yield advantage under disease pressure would be expected for ND Falcon compared with other pinto bean cultivars while eliminating or reducing the need for fungicide and/or nematicide applications. ND Falcon has desirable upright architecture (type IIa) with short vines. Under North Dakota conditions, ND Falcon shows an average plant height of 53 cm, has a 100‐seed weight of 37.0 g, and matures in approximately 103 d. Other traits of agronomic or economic importance are within acceptable commercial ranges for pinto bean.